The Common Agricultural and Food Policy of the European Union: An Assessment of its Framework, Stages and Regulations - Halil Günay (International Journal of Gastronomy Research)
Agriculture (production) and food (consumption) are two important political fields that affect each other and have direct links. Agriculture and food, which have a vital function in human life, affect many areas, especially the economy of farmers and people and are interrelated. Therefore, the Common Agricultural and Food Policy is one of the most important common policy areas for the European Union, both in terms of budget and other common policies. The importance of this common policy increases especially for the smooth and smooth functioning of the common market. In this context, this study investigates the Treaty of Rome establishing the European Economic Community of the European Union and the Common Agricultural Policy established in line with the Treaty's objective of establishing a common market. Under the influence of global and regional events, state and non-state actors have protectionist and revisionist tendencies in some political areas. The European Union, which is an important non-state actor in the international system in global and regional areas, has made protectionist-centered revisions in some political areas due to both its internal dynamics and the global and regional events in the system. One of the political areas in which the European Union has made revisions is the Common Agricultural Policy. The Common Agricultural Policy of the European Union has been updated in line with its needs, especially regarding food security and reducing greenhouse gas emissions to zero.